2013
DOI: 10.1007/s11356-013-1908-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi on Agrostis capillaris grown on amended mine tailing substrate at pot, lysimeter, and field plot scales

Abstract: Applied research programs in the remediation of contaminated areas can be used also for gaining insights in the physiological and ecological mechanisms supporting the resistance of plant communities in stress conditions due to toxic elements. The research hypothesis of this study was that in the heavily contaminated but nutrient-poor substrate of mine tailing dams, the beneficial effect of inoculation with arbuscular mychorrizal fungi (AMF) is due to an improvement of phosphorus nutrition rather than to a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…It is documented that the mycorrhizae are involved in nutrient transfer to the plant by increasing root surface, extending the nutrient depletion area around the root, and making phosphorus and nitrogen sources available to the plant [43]. Recently, Doubková et al [44] found that inoculation improves plant growth and increases phosphorus uptake, which is in line with this result and our other previous results [13,14].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…It is documented that the mycorrhizae are involved in nutrient transfer to the plant by increasing root surface, extending the nutrient depletion area around the root, and making phosphorus and nitrogen sources available to the plant [43]. Recently, Doubková et al [44] found that inoculation improves plant growth and increases phosphorus uptake, which is in line with this result and our other previous results [13,14].…”
Section: Resultssupporting
confidence: 85%
“…This is the order of pollution increase, too, similar results also being published by González-Guerrero et al [53] and, Neagoe et al [13,14]. What is interesting, in contrast with very contaminated substrates such as mine tailings [12][13][14], is that the response of oxidative stress variables for plants grown in unpolluted or slightly polluted soils presents similar patterns of variation in almost all plant parts. However, plants benefit from the effect of mycorrhizal fungi even in such substrates because the fungi enhance drought resistance in them [17,54].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Neagoe et al [54] found similar positive correlations between protein and P nutrition in the case of four plant species grown on a metal-contaminated soil. Also, in a recent study, [55,56] it was shown that P nutrition strongly influenced the development of Agrostis capillaris on a mine tailing substrate, alleviating the oxidative stress and increasing the protein content. We found the same variation pattern in the case of the enzymatic activities, but not in the case of lipid peroxides in plantain, whose concentration was below the detection limit of the used method (Table 10).…”
Section: Oxidative Stressmentioning
confidence: 98%
“…The additional value of this data is related to the fact that Agrostis capillaris is our model plant species and other raw data sets about it will be reported in the future, corresponding to existing [2,3] and future publications. This will allow improve the potential for metadata analysis.…”
mentioning
confidence: 99%